Yasmin Induced Pulmonary Embolism: a Case Report - Xiangjun, Zhu; Yin, Chen; Yuehua, Yang; Zhiming, Sun (Journal of Advanced Pharmaceutical Science And Technology, 2021)
We evaluate a case report of Yasmin induced pulmonary embolism in order to provide reference for safety use of oral contraceptives.
Keywords: Yasmin; Oral contraceptive; Pulmonary embolism.